Daratumumab as Single Agent in Relapsed/Refractory Myeloma Patients: A Retrospective Real-Life Survey - Markovic, Uros; Romano, Alessandra; Del Fabro, Vittorio; Bellofiore, Claudia; Bulla, Anna; Parisi, Marina Silvia; Leotta, Salvatore; Gentile, Massimo; Cangialosi, Clotilde; Vincelli, Iolanda; Mineo, Giuseppe; Rossi, Marco; et al. (Frontiers in Oncology, 2021)
Background: The anti-CD38 monoclonal antibody daratumumab is approved as a single agent for the treatment of patients with relapsed/refractory multiple myeloma (RRMM) who received at least three prior lines of therapy, including proteasome inhibitor and immunomodulatory agent. A retrospective multicentric study was designed to evaluate feasibility, tolerability and efficacy of daratumumab in monotherapy in RRMM. Methods: This study included 44 consecutive RRMM patients that underwent daratumumab monotherapy after a median number of 4 prior therapies (range 2-9). Patients were treated in seven Sicilian centers, as part of Sicilian Myeloma Network and three Calabrian centers outside of controlled clinical trials from August 2016 through July 2020. Results: The regimen was well tolerated with few grade 3-4 haematological and rare non-haematological adverse events, such as pneumonia. Definitive discontinuation was due to disease progression in 25 (57%) patients. Since 3 patients did not complete at least one full cycle, a total of 41 patients was evaluated for response. Overall response rate was 37%, and the disease control rate (stable disease or better) was high (73%). The best achieved responses within 6 months were very good partial remission or better (27%), partial remission (10%), minimal response (14%) and stable disease (22%). After a median follow up of 7.8 months, median progression free survival (PFS) was 7.2 months and overall survival (OS) 7.8 months. Univariate analysis showed that patients with PR or better after 6 months of therapy had longer median PFS and OS (respectively 29.5 vs 3.6 months, p=0.0001 and 30.6 vs 3.9 months p=0.0001), confirmed by multivariate analysis. Furthermore, standard cytogenetic risk and biochimical relapse type had prolonged median PFS, but not OS (respectively unreached vs 2.6, p=0.03 and 23.9 vs 6.2, p=0.05) in both univariate and multivariate analysis. Additionally, univariate analysis showed that patients treated with carfilzomib-lenalidomide-dexamethasone prior to daratumumab had significantly shorter PFS compared to pomalidomide-dexamethasone (9.3 vs 3.4 months, p=0.03), that multivariate analysis failed to confirm. Conclusions: Our findings indicate that daratumumab as single agent is safe and well-tolerated regimen in real-life, associated to prolonged PFS and OS in responding patients. No new safety signals were identified.